Measuring people’s covariational reasoning in Bayesian situations - Steib, Nicole; Krauss, Stefan; Binder, Karin; Büchter, Theresa; Böcherer-Linder, Katharina; Eichler, Andreas; Vogel, Markus (Frontiers in Psychology, 2023)
Previous research on Bayesian reasoning has typically investigated people’s ability to assess a posterior probability (i.e., a positive predictive value) based on prior knowledge (i.e., base rate, true-positive rate, and false-positive rate). In this article, we systematically examine the extent to which people understand the effects of changes in the three input probabilities on the positive predictive value, that is, covariational reasoning. In this regard, two different operationalizations for measuring covariational reasoning (i.e., by single-choice vs. slider format) are investigated in an empirical study with N = 229 university students. In addition, we aim to answer the question wheter a skill in “conventional” Bayesian reasoning is a prerequisite for covariational reasoning.